Enabling significant public contribution to urban redesign with open-source 3D modeling software. - Likuski, Andy. (2017)
Abstract: This paper explores the potential of open-source software to empower the public to contribute persuasive streetscape redesigns that promote carfree space and modern, comprehensive transit systems. A software plugin named Rescape that works in conjunction with the 3D modeling program Google Sketchup was developed. Rescape is open-source software (though Sketchup is not) that guides users through the process of performing a redesign of an existing urban space of their choice. It provides custom tools, including the ability to download and render road data for their area of choice, as well as a variety of tools to ease the layout of useful streetscape elements such as streetcar tracks, sidewalks, and trees that are aligned with the downloaded road data. Rescape enables users to quickly create the foundations of a realistic site redesign model that can then be augmented by Sketchup's built-in tools and large collection of free 3D components. The software's ultimate goal is to help the public create and share ideas that advance carfree urban spaces with modern rail-based transit as an alternative to the current car-oriented allocation of public space.; Thesis (M.A.)--Tufts University, 2012.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Mark Chase.; Committee: Ann Rappaport.; Keywords: Urban planning, and Transportation planning.